2020
DOI: 10.1016/j.jsxm.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Barriers and Facilitators to Seeking and Accessing Support in Gynecologic and Breast Cancer Survivors with Sexual Problems: A Systematic Review of Qualitative and Quantitative Studies

Abstract: Background Greater understanding of patient-reported barriers and facilitators to seeking and accessing sexual health services will help formulate strategies to assist gynecologic and breast cancer patients to overcome obstacles to accessing sexual health support because they typically do not seek sexual education and/or treatment when confronted with sexual concerns. Aim The objectives of this systematic review were to (i) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…Of these, more than half indicated a lack of help in addressing sexual problems from health care professionals. In addition, older patients are less likely to report sexual problems than younger patients [13,14]. Similar conclusions were formulated by Gleeson and Hazell who found that most healthcare professionals do not routinely assess the sexual well-being of patients receiving palliative care.…”
Section: Discussionsupporting
confidence: 71%
“…Of these, more than half indicated a lack of help in addressing sexual problems from health care professionals. In addition, older patients are less likely to report sexual problems than younger patients [13,14]. Similar conclusions were formulated by Gleeson and Hazell who found that most healthcare professionals do not routinely assess the sexual well-being of patients receiving palliative care.…”
Section: Discussionsupporting
confidence: 71%
“…Standardised instruments (questionnaires) may help to assess the grade of impairment. [136][137][138][139][140] At first recurrence, one out of four patients is younger than 50 years old and premenopausal. Therefore, issues of fertility and contraception must be discussed, and for the latter, only hormone-free contraceptives can be recommended.…”
Section: Iv/b 86%mentioning
confidence: 99%
“…Patient advocates and studies have strongly emphasized and recognized that there needs to be more support and treatment, such as for those who experience sexual dysfunction, and its long-term consequences on mental well-being. 20 Therefore, collection of patient experience data throughout the breast cancer clinical development program could help inform tolerability of new therapies, with an emphasis on patient-reported symptoms, side-effects, physical function, ability to work, and healthrelated quality of life. Additionally, the breast cancer clinical development program should reflect the racial and ethnic diversity of this patient population.…”
mentioning
confidence: 99%